Skyping the Family : Interpersonal Video Communication and Domestic Life. - Harper, Richard. (Benjamins Current Topics Series, 2019)
This collection is one of the first in-depth studies of video calling in family and domestic life. Originally published as a special issue of Pragmatics, issue 27:3 (2017).